Increasing Capsicum Yield, Nitrogen Use Efficiency and Profits through Optimal Nitrogen Fertilizer Application in Naturally Ventilated Polyhouse - Timilsina, Sandip; Khanal, Asmita (Nepalese Horticulture, 2024)
Most of the farmers in mid-hill areas introduce plastic houses, naturally ventilated poly-houses or other types of protected structures for year-round vegetable production. Capsicum is a commonly cultivated crop inside these structures. Optimizing nitrogen (N) fertilization during capsicum production is critical for increasing crop yields, increasing nitrogen use efficiency (NUE), increasing net profit of farmers and minimizing the loss of nutrients into the environment. A study was carried out to identify the optimal nitrogen dose for enhancing Capsicum yield, nitrogen use efficiency (NUE), and net profits within a naturally ventilated polyhouse at the Directorate of Agriculture Research, Lumle, Kaski, Nepal, in two consecutive years; 2019 and 2020. Eight nitrogen levels (0, 100, 125, 150, 175, 200, 225, and 250 kg/ha) were evaluated using a randomized complete block design with three replications. Data were collected on each treatment’s effect on yield, yield-related characteristics, nitrogen use efficiency (NUE), and production cost. Nitrogen application at 225 kg/ha resulted the highest fruit yield and net benefit; however, N levels between 200 and 250 kg/ha showed similar effect on yield, yield-related components and net benefit. Considering agronomic, economic, and NUE factors, an N dose of 200 kg/ha along with 30 t/ha farmyard manure (FYM) was found to be optimal for Capsicum cultivation in a naturally ventilated polyhouse at Lumle, Kaski, and this N dose can be recommended for similar soil and agroecological conditions in Nepal.